Pembentukan Karakter Religius dan Mandiri Melalui Model Pendidikan Ala Pondok Pesantren - Ubaidillah, Aan Fardhani (AL-WIJDÃN Journal of Islamic Education Studies, 2016)
This paper aims to describe the role of education which is conducted by Islamic boarding schools in shaping religious and independent characters. The research method used in this paper is a library study by conducting content analysis from various books, research journals, and conceptual journals about Islamic boarding schools. The conclusion of the study is the education model in Islamic boarding schools to shape the religious and independent characters is conducted through continuous education during theoretical and literary face-to-face activity as well as daily practice of the students in a conducive applicative environment. Other characters that are also developed in Islamic boarding schools are (1) Religious character in a humanistic relationship with God (hablun min Allah) with faith and devotion as the main values which are established through mandatory and Sunnah religious rituals; its practice goes along with the strengthening of humanity religious value (hablun min naas) which covers the characters of (a) togetherness, caring, and affection, (b) simplicity, respect, and politeness, (c) responsibility, honesty, and sincerity, and (2) the independent character is shaped through the chance given to the students to self-organized the activities and organization in the Islamic boarding school as well as their daily activities in togetherness, simplicity, and teamwork. The establishment of religious and independent characters are based on these twelve principles: (1) reality-based activity, (2) good example from the teachers, (3) ‘Teacher, not Worker’, (4) affection-based learning method, (5) student as subject, (6) learning for work, (7) self-identity discovery, (8) the establishment of independence and togetherness, (9) life skill education, (10) never stop learning and working, (11) creating a conducive and caring environment, and (12) soul-nurturing and riyadah. Keywords: character, independent, Islamic boarding school